ILLEGITIMITY OF THE PUBLIC MINISTRY TO PROPOSE REVISÃO CRIMINAL: FISCAL LAW? (Reflection and Critique Law Magazine, 2020)
The article starts from the importance on the theme of motivation within organizations, an attempt was made in the present study to provoke a discussion about a legislative omission with respect to the Legitimacy of the Public Ministry to use the Revisão Criminal institute, since, this is the “Inspector of the law” and therefore more than legitimate to defend society from injustices and arbitrariness.Due to the absence of doctrines in the area, a study purchased between the Public Ministry, its functions, guarantees and principles was used, with the legal nature of Revisão Criminal.Finally, the aforementioned work has as its central objective, to identify different points of view on a topic little debated within the academic environment, exploring in a succinct way brief expositions on the subject based on doctrine, jurisprudence and even articles spread across the world wide web. computers.Key words: Public Ministry; Justice promoter; Revisão Criminal; Illegitimacy.